PENGARUH MODEL PEMBELAJARAN HEURISTIK VEE BERBANTUAN MEDIA VIDEO TERHADAP HASIL BELAJAR IPA DITINJAU DARI MOTIVASI BELAJAR - Pradani, Ni Made Ninda (Universitas Pendidikan Ganesha, 2018)
This study aims to 1) describe and explain the differences in science learning outcomes between students who follow the Vee Heuristic learning model assisted by video media with direct learning models, in class VIII in SMP Negeri 5 Denpasar, 2) describe and explain differences in science learning outcomes, between students who followed the Vee Heuristic learning model with students who followed the direct learning model in groups of students who had high learning motivation, 3) described and explained the differences in science learning outcomes between students who followed the Vee Heuristic learning model, with students who followed the direct learning model in groups students who have low learning motivation. The population in this study were all students class VIII SMP Negeri 5 Denpasar which amounted to 386, with a sample of 64 people taken at random. Learning outcomes data, collected by learning outcomes test, while learning motivation data collected by questionnaire. Data were analyzed by using two-way ANOVA analysis and continued with Tukey test. The results showed that: (1) there are differences in science learning outcomes among students who followed the Vee Heuristic model assisted by video media, with students who took the direct learning model for eighth grade students in SMP Negeri 5 Denpasar with a significance value of 0.001 in